Potential for Blood Glucose Reduction by Indonesian Plant Leaf Extracts: Systematic Review of in Vivo Studies - Made Devina Febryanti; I Putu Adi Wibowo; I Made Lingga Tresnadinata; Ni Putu Cempaka Pradnyadewi; Made Ayu Rahayu Agastyane Rahmadewi (Jurnal Sehat Indonesia (JUSINDO), 2026)
Introduction: Diabetes mellitus is a chronic disease characterized by persistent hyperglycemia. The rising prevalence of diabetes has increased interest in alternative therapies, including herbal medicines. Indonesia has abundant medicinal plants whose leaf extracts contain bioactive compounds with potential antidiabetic effects, yet scientific evidence regarding their effectiveness remains fragmented. Purpose: Therefore, this study aims to systematically review the potential of Indonesian plant leaf extracts in reducing blood glucose levels based on in vivo experimental studies. Method: A systematic review was conducted by following the PRISMA guidelines through a literature search on the Google Scholar and Science Direct databases. The articles analyzed were original studies published between 2020 and 2025 that focused on in vivo studies examining the potential of various leaf extracts to reduce blood glucose levels. Discussion: Phytochemical analysis indicates that leaf extracts may act effectively by providing antioxidant protection to pancreatic beta cells, increasing GLUT4 expression, and inhibiting digestive enzymes. Although their effects can rival standard drugs with a lower risk of hypoglycemia, the current literature still has limitations, particularly the short duration of in vivo testing and the lack of chronic toxicity data. Conclusion: Indonesian plant leaf extracts show promising potential as natural antihyperglycemic agents; nevertheless, further studies involving long-term toxicity evaluation, standardized extraction methods, and clinical trials are required to confirm their safety and effectiveness in humans.